The Relationship between Environmental Management Practices and Environmental Performance: The Role of Organisational Culture (Journal of Business Management and Accounting, 2013)
Nowadays, organisations and their management are working very hard to forecast and respond to ever-changing new markets and fierce competition. Due to increase in globalisation and technological advancements, the constant variable for today’s workplace is perhaps the ability to continuously evolve. Organisations must ensure that their activities do not harm or negatively impact the environment. This study investigated the effect of organisational culture on the relationship between environmental management practice and environmental performance. Organisational culture was measured using an adapted version of the Henri’s 2006 instrument which was based on a competing values perspective. Questionnaires were administered to 300 respondents (general managers/general managers) from various hotels in the Malaysian hotel industry. The hierarchical multiple regression method showed that organisational culture is not significantly related to environmental performance. However, to some extent, organisational culture has moderated the relationship between environmental management practice and environmental performance. This result implied that most of the sampled hotels in Malaysia employed a control dominant type of culture in achieving objectives. The results also showed even though hotels create an environmental culture in their activities, if people are not ready and not willing to share their knowledge toward creation of new values and beliefs, better environmental performance will not be achieved. This insignificant finding may be due to new beliefs relating to environmental issues in the Malaysian hotel industry.